The Recruitment and Immune Suppression Mechanisms of Myeloid‐Derived Suppressor Cells and Their Impact on Bone Metastatic Cancer - Chengyuan Li; Yucheng Xue; Eloy Yinwang; Zhaoming Ye (Cancer Reports)
ABSTRACT Background MDSCs are immature neutrophils and monocytes with immunosuppressive potentials, involving mononuclear MDSCs (M‐MDSCs) and polymorphonuclear MDSCs (PMN‐MDSCs). Recent Findings They are significant components of the tumor microenvironment (TME). Besides, recent studies also verified that MDSCs also facilitated the progression of bone metastasis by regulating the network of cytokines and the function of immune cells. Conclusion It is necessary to summarize the mechanisms of MDSC recruitment and immunosuppression, and their impact on bone metastasis.